Concise enantioselective synthesis of (+)-L-733,060 and (+)-T-2328 via sequential proline catalysis - Lalwani, Komal G.; Sudalai, Arumugam (Synlett, 2016)
A new, sequential proline-catalyzed approach to the synthesis of (+)-L-733,060 and (+)-T-2328 in high optical purity (93% ee) is described starting from phenyl N-Boc imine. The strategy involves proline-catalyzed Mannich reaction of an arylimine with acetaldehyde followed by -aminoxylation/Wittig olefination in a sequential fashion as the key steps.
Keywords: Aminoxylation; imine; Mannich reaction; olefination; sequential